2021
DOI: 10.1158/0008-5472.can-20-3607
|View full text |Cite
|
Sign up to set email alerts
|

Supraphysiologic Testosterone Induces Ferroptosis and Activates Immune Pathways through Nucleophagy in Prostate Cancer

Abstract: The discovery that androgens play an important role in the progression of prostate cancer led to the development of androgen deprivation therapy (ADT) as a first line of treatment. However, paradoxical growth inhibition has been observed in a subset of prostate cancer upon administration of supraphysiologic levels of testosterone (SupraT), both experimentally and clinically. Here we report that SupraT activates cytoplasmic nucleic acid sensors and induces growth inhibition of SupraT-sensitive prostate cancer c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…SPA can be provided to cells as R1881, a potent synthetic androgen that is not metabolized in vitro , at a dose of 10nM, which is approximately 20-fold higher than the level of free testosterone in eugonadal adult men. LNCaP and VCaP cell lines are growth-inhibited by SPA, while LAPC4 and 22Rv1 cell lines exhibit primary resistance to SPA (Fig 1a) [1,9,10]. Among these cell lines, we observed that pre-treatment AR abundance and activity (as assessed by expression of the AR target PSA) was higher in SPA-sensitive cell lines than SPA-resistant cell lines (Fig 1b).…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…SPA can be provided to cells as R1881, a potent synthetic androgen that is not metabolized in vitro , at a dose of 10nM, which is approximately 20-fold higher than the level of free testosterone in eugonadal adult men. LNCaP and VCaP cell lines are growth-inhibited by SPA, while LAPC4 and 22Rv1 cell lines exhibit primary resistance to SPA (Fig 1a) [1,9,10]. Among these cell lines, we observed that pre-treatment AR abundance and activity (as assessed by expression of the AR target PSA) was higher in SPA-sensitive cell lines than SPA-resistant cell lines (Fig 1b).…”
Section: Mainmentioning
confidence: 99%
“…These data suggest that SPA inhibits growth of CRPC with high AR abundance in part through downregulation of MYC. We anticipate that MYCindependent maladaptive effects of SPA may also contribute to growth inhibition, including AR inhibition of DNA relicensing during mitosis [20], AR-mediated DNA damage [21,22], and induction of ferroptosis and immunogenic cell death [10].…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone at supraphysiologic doses in men with CRPC has been reported to produce promising results [ 43 , 44 ], with trials suggesting a clinical benefit in a subset of patients [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Checkpoint-blocking antibodies targeting CTLA-4, PD-1, and PD-L1 may, on the other hand, promote T cell glycolysis and IFN production by restoring pH in the TME [ 59 ]. Consequently, LDH-A increases antitumor immunity in bone marrow cells by stimulating Th17 cells to control angiogenesis and PDL1 expression; consequently, LDH-A inhibitors may provide a unique strategy for increasing the effectiveness of checkpoint inhibitors [ 60 ]. Dichloroacetate (DCA) decreases tumor cell glycolysis in melanoma [ 61 ] and also enhances the immunosuppressive state generated by lactate, hence increasing the efficacy of anticancer immunotherapy.…”
Section: Introductionmentioning
confidence: 99%